62 A MOUSE MODEL OF HEMOCHROMATOSIS EXHIBITS DECREASED INSULIN SECRETORY CAPACITY COMPENSATED BY INCREASED INSULIN SENSITIVITY, AND RESISTANCE TO DIET-INDUCED OBESITY. (1st January 2005) - Sanderson, M.; Jones, D.; Jouihan, H.; Ajioka, R.; Cooksey, R.; Kushner, J.; McClain, D.
Abstract : Nondiabetic subjects with iron overload secondary to hereditary hemochromatosis exhibit decreased insulin secretory capacity without insulin resistance. Similarly, in a mouse model with deletion of the HFE gene (Hfe-/-), islets undergo iron-induced glucose desensitization and apoptosis, but normal glucose tolerance is maintained. On normal chow, weights of the Hfe-/- and wildtype (WT) mice are similar (30±1 g in WT vs 29±2 in Hfe-/-). During a euglycemic hyperinsulinemic clamp (20 mU/kg/min), Hfe-/- mice have similar glucose disposal rates to WT (167±13 mg/kg/min in Hfe-/- compared to 175±13 in WT) with complete suppression of hepatic glucose production in both groups. At submaximal insulin (5 mU) however, hepatic glucose production remains suppressed in Hfe-/- while in WT it is 48±35 mg/kg/min (p=0.02). This results in a 42% reduction in glucose turnover rates in the Hfe-/- mice (p≤0.05). After a 6 week challenge with a high fat diet, the Hfe-/- mice weigh less (32±1 vs 37±2 g, p=0.02). Intraperitoneal glucose tolerance testing (GTT) revealed significantly better glucose tolerance in the Hfe-/- (incremental AUC = 6.4±1.1 g.min/dl in Hfe-/- vs. 9.5±0.6 in WT, p=0.03), but values were similar when controlled for weight. This occurs despite a 26% reduction in fasting insulin and a 38% reduction in insulin at 30 min of the GTT in the Hfe-/- mice. On the high fat diet, adiponectin levels tend to be slightly higher in the Hfe-/- (40±12 vs 35±3 μg/ml, p=NS), while free fatty acids, triglycerides, and resistin are similar. In a metabolic chamber, Hfe-/- mice, despite weighing less, eat slightly more (7 μg/g body weight, p=NS) and exhibit a 9% increase in heat production (p≤0.001) and a 12% increase in oxygen consumption with similar levels of activity. We conclude that iron overload leads to an insulin secretory defect, but this is compensated by increased insulin sensitivity, largely at the level of hepatic glucose production. The Hfe-/- mice are also resistant to diet induced obesity and insulin resistance, possibly on the basis of uncoupled metabolism. Whether this is mediated by central or peripheral mechanisms is under investigation.